Primary Cutaneous Cryptococcosis Case Report - M. Sanches, Carlos E. (2018)
Cryptococcosis is a disease caused by the fungus Cryptococcus neoformans, commonly found in bird excrement, like pigeons. This organism has the ability to cause disease in humans, which may affect several organs, including the skin. Most commonly it causes disease in individuals with some kind of suppression of the immune system. The case reported is of a female patient of 44-years- -old that had used corticosteroids for many months without prescription and presented a skin lesion on her left arm. Laboratory tests confirmed the diagnosis of primary cutaneous cryptococcosis.